PROFIL PROFESIONALISME DOSEN JURUSAN PENDIDIKAN BAHASA INGGRIS - Ni Made Ratminingsih (Universitas Pendidikan Ganesha, 2015)
Abstract: The Profile of Lecturers’ Professionalism of English Education Department. The aim of this research was to describe the lecturers’ professionalism at English Education Department in academic year 2011/2012. This was a descriptive research with a survey method, which was carried out by distributing questionnaires. They were 200 students of English Education Department sprea-ding from semester 1 to semester 7 from ten classes as the samples of the study. They were deter-mined purposively by taking into consideration as to whether the class was taught by the lecturer whom they were assessed.The finding proves that (1) the lecturers’ professionalism of English Edu-cation Department was assessed good by the students (mean: 3.72), (2) from the four competencies, personality competency reached the highest score (mean: 3.93), followed by social competency (mean: 3.88), professional competency (mean: 3.76), and finally pedagogicalcompetency (mean: 3.31), and (3) compared to other competencies, pedagogical competency was assessed the lowest among others and was classified moderate. Keywords: competency, professionalism Abstrak: Profil Profesionalisme Dosen Jurusan Pendidikan Bahasa Inggris. Tujuan utama pene-litian ini adalah untuk mengkaji profesionalisme staf dosen Jurusan Pendidikan Bahasa Inggris tahun akademik 2011/2012. Penelitian ini merupakan penelitian deskriptif dengan metode survei, yaitu melalui penyebaran angket kepada responden, yakni 200 mahasiswa dari semester 1 sampai dengan semester 7 dari sepuluh kelas, yang ditentukan secara purposif berdasarkan kelas-kelas yang diajar oleh para dosen yang bersangkutan. Hasil penelitian membuktikan bahwa (1) secara umum kom-petensi dosen Jurusan Pendidikan Bahasa Inggris adalah baik (rerata: 3,72), (2) dari keempat kom-petensi yang dinilai, kompetensi kepribadian mendapatkan capaian tertinggi (rerata 3,93) yang di-ikuti oleh kompetensi sosial (rerata 3,88), kompetensi profesional (rerata 3,76), dan terakhir kompe-tensi pedagogik (rerata 3,31), dan (3) dibandingkan dengan kompetensi lainnya, kompetesi pedago-gik dinilai paling rendah oleh mahasiswa, dengan kategori cukup. Kata-kata Kunci: profesionalisme, kompetensi